Investigations into the impact of non-coding RNA on the sensitivity of gastric cancer to radiotherapy - Usman, Muhammad; Beilerli, Aferin; Sufianov, Albert; Kudryashov, Valentin; Ilyasova, Tatiana; Balaev, Pavel; Danilov, Andrei; Lu, Hong; Gareev, Ilgiz (Frontiers in Physiology, 2023)
Non-coding RNAs (ncRNAs) are a newly discovered functional RNA different from messenger RNA, which can participate in regulating the occurrence and development of tumors. More and more research results show that ncRNAs can participate in the regulation of gastric cancer (GC) radiotherapy response, and its mechanism may be related to its effect on DNA damage repair, GC cell stemness, cell apoptosis, activation of epidermal growth factor receptor signaling pathway, etc. This article summarizes the relevant mechanisms of ncRNAs regulating the response to radiotherapy in GC, which will be directly important for the introduction of ncRNAs particularly microRNAs (miRNAs), long non-coding RNAs (lncRNAs) and circular RNAs (circRNAs) into clinical medicine as biomarkers and therapeutic targets.